Anti-aging high-strength ABS composite material and preparation method thereof

By introducing a gradient structure layered metal oxide PVC film layer into ABS resin, the synergistic effect of CeO2-LDHs and Mg-Al-LDHs is used to solve the problem of poor aging resistance performance of ABS resin products, and significantly improve its aging resistance and Mechanical properties.

CN119502500APending Publication Date: 2025-02-25CHANGZHOU YONGJIE PLASTIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411599006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Because ABS resin products contain butadiene components, they have poor aging resistance, are prone to discoloration and cracking, and are insufficient impact strength and toughness, and have limited application scope.

Method used

The PVC film layer with a gradient structure is used to recombine with ABS, and the aging resistance and mechanical properties of ABS are improved through the synergistic effect of CeO2-LDHs and Mg-Al-LDHs.

Benefits of technology

It significantly improves the aging resistance and mechanical properties of ABS composites, including the improvement of UV resistance, impact strength and thermal deformation temperature, and expands the application range of materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of an anti-aging high-strength ABS (acrylonitrile butadiene styrene) composite material, which comprises the following steps: S1, mixing Mg-Al-LDHs (layered double hydroxides) and ABS rubber powder, mixing a blend by adopting a three-screw extruder, and shearing and granulating by adopting a granulator; s2, the blend is subjected to tape casting and sheet pulling through a tape casting machine, and an ABS sheet is obtained; and S3, performing hot press molding on the ABS sheet and the layered metal oxide PVC film with the gradient structure by adopting a hot press, compounding one side of the PVC film with low CeO2-LDHs content with the ABS sheet, performing hot press, then performing water cooling, mold opening and trimming, and finally performing drying by adopting a drying oven to obtain the ABS composite material. According to the ABS composite material disclosed by the invention, the layered metal oxide PVC film layer with the gradient structure is compounded with the ABS, so that the aging resistance and the mechanical property of the ABS are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to an aging-resistant high-strength ABS composite material and a preparation method thereof. Background Art

[0002] Poly ABS resin is one of the five general-purpose plastics and is widely used. Compared with other general-purpose plastics, ABS resin has good flow, rigidity and other properties and excellent appearance quality. This is determined by the structure and composition of ABS resin. ABS resin is copolymerized by three monomers: acrylonitrile, butadiene and styrene. Styrene monomer provides excellent flow properties, acrylonitrile monomer provides rigidity and chemical resistance, and butadiene monomer provides toughness. It is precisely because of this structure that ABS resin has obvious disadvantages: the polybutadiene component has poor aging resistance, so ABS resin products are easy to discolor and are not suitable for outdoor use. Although ABS has many advantages, due to the double bonds generated by butadiene, it has poor weather resistance and is prone to aging, discoloration, and even cracking when exposed outdoors for a long time, thereby reducing the impact strength and toughness of the material. It is flammable and has a low heat deformation temperature. Therefore, it is necessary to modify it to enhance its impact strength, toughness and heat deformation temperature in order to expand the application range of the material. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide an aging-resistant high-strength ABS composite material, which is compounded with ABS using a layered metal oxide PVC film layer with a gradient structure to improve the aging resistance and mechanical properties of ABS.

[0004] Technical solution: An aging-resistant high-strength ABS composite material, the ABS composite material comprising an anti-ultraviolet layer and an ABS layer, the anti-ultraviolet layer being composed of a layered metal oxide PVC film with a gradient structure. Preferably, the method for preparing the anti-ultraviolet layer comprises the following steps: S11. CeO2 was added to deionized water and ultrasonically dispersed uniformly, and then Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added and stirred with ultrasonic heating, and then hydrothermally reacted to obtain CeO2-LDHs; S12. CeO2-LDHs was added to tetrahydrofuran, stirred and mixed evenly, and CeO2-LDHs suspensions with different concentrations were prepared; S13. The polyvinyl chloride and the photosensitizer were dissolved in tetrahydrofuran to obtain a PVC solution, and CeO2-LDHs suspensions of different concentrations were added, and the suspensions were stirred and dispersed uniformly to obtain PVC-LDHs dispersions of different concentrations; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. The method for preparing the above-mentioned aging-resistant high-strength ABS composite material comprises the following steps: S1. Mixing Mg-Al-LDHs and ABS rubber powder, mixing the blend by a three-screw extruder, and then shearing and granulating the mixture by a granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. Use a hot press to hot-press the ABS sheet and the gradient structure layered metal oxide PVC film, and compound one side of the PVC film with low CeO2-LDHs content with the ABS sheet. After hot pressing, water-cool, mold opening, trimming, and finally drying in an oven to obtain an ABS composite material. Preferably, in step S11, the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea is 9-13:18-25:40-50:22-28, the temperature of heating and stirring is 85-95°C, the time is 1-2h, and the temperature of hydrothermal reaction is 110-120°C, and the time is 2-3h. Preferably, in step S12, the concentration of the high-concentration CeO2-LDHs suspension is 3.5-5.5wt%, and the concentration of the low-concentration CeO2-LDHs suspension is 1.5-3wt%. Preferably, in step S13, the concentration of polyvinyl chloride in tetrahydrofuran is 5-8wt%, and the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1. Preferably, in step S1, the mass ratio of Mg-Al-LDHs to ABS rubber powder is 1-2:100. Preferably, in step S3, the hot pressing adopts different upper and lower hot pressing temperatures: the hot pressing temperature on the PVC film side is 180-190°C, the hot pressing temperature on the ABS sheet side is 190-210°C, the hot pressing time is 1.5-3min, and the pressure is 1-3Mpa. Beneficial effects: The aging-resistant high-strength ABS composite material of the present invention has the following advantages: 1. In the present invention, the layered metal oxide PVC film layer with a gradient structure is compounded with ABS. The outer layer of the PVC film contains more CeO2-LDHs, which can absorb and reflect more ultraviolet rays during ultraviolet radiation. The PVC side compounded with ABS contains a small amount of CeO2-LDHs. The layer contains a small amount of CeO2-LDHs, which can achieve secondary absorption and reflection, thereby improving the anti-aging effect of the ABS composite material; 2. The present invention uses CeO2 composite LDHs, and the synergistic effect of rare earth oxides and LDHs can further improve the effect of ultraviolet absorption and reflection; 3. In the present invention, Mg-Al-LDHs is also added to ABS. Mg-Al-LDHs can not only cooperate with the PVC film layer to improve the anti-ultraviolet effect, but also achieve the effect of mechanical enhancement and improve the strength of ABS. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film containing a low amount of CeO2-LDHs is compounded with the ABS sheet. The hot pressing temperature is 180°C on the PVC film side and 190°C on the ABS sheet side. The hot pressing time is 3 minutes and the pressure is 1 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain an ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After adding CeO2 to deionized water and dispersing it uniformly by ultrasonic, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added, and the mixture was heated to 85°C and stirred for 2h by ultrasonic, and then subjected to hydrothermal reaction at a temperature of 120°C for 2h to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 9:18:40:22; S12. CeO2-LDHs was added to tetrahydrofuran, and stirred to mix uniformly to prepare CeO2-LDHs suspensions of different concentrations, wherein the concentration of the high-concentration CeO2-LDHs suspension was 3.5wt%, and the concentration of the low-concentration CeO2-LDHs suspension was 1.5wt%; S13. Dissolving polyvinyl chloride and a photosensitizer in tetrahydrofuran to obtain a PVC solution, wherein the concentration of polyvinyl chloride in tetrahydrofuran is 5 wt %, adding CeO2-LDHs suspensions of different concentrations, and the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1, and after stirring and dispersing uniformly, obtaining PVC-LDHs dispersions of different concentrations; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Example 2 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 2:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film containing a low amount of CeO2-LDHs is compounded with the ABS sheet. The hot pressing temperature is 190°C on the PVC film side and 210°C on the ABS sheet side. The hot pressing time is 1.5 min and the pressure is 3 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain the ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After adding CeO2 to deionized water and dispersing it uniformly by ultrasonic, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added, and the mixture was heated to 95°C and stirred for 1 hour by ultrasonic, and then subjected to hydrothermal reaction at a temperature of 110°C for 3 hours to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 13:25:50:28; S12. CeO2-LDHs was added to tetrahydrofuran, and stirred to mix uniformly to prepare CeO2-LDHs suspensions of different concentrations, wherein the concentration of the high-concentration CeO2-LDHs suspension was 5.5wt%, and the concentration of the low-concentration CeO2-LDHs suspension was 3wt%; S13. The polyvinyl chloride and the photosensitizer are dissolved in tetrahydrofuran to obtain a PVC solution, wherein the concentration of the polyvinyl chloride in tetrahydrofuran is 8 wt %, and CeO2-LDHs suspensions of different concentrations are added, wherein the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1, and after being stirred and dispersed uniformly, PVC-LDHs dispersions of different concentrations are obtained; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Example 3 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. The Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1.2:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film containing a low amount of CeO2-LDHs is compounded with the ABS sheet. The hot pressing temperature is 185°C on the PVC film side and 195°C on the ABS sheet side. The hot pressing time is 2.5 min and the pressure is 2.5 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain an ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After adding CeO2 to deionized water and dispersing it uniformly by ultrasonic, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added, and the mixture was heated to 85°C and stirred for 2h by ultrasonic, and then subjected to hydrothermal reaction at a temperature of 110°C for 3h to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 12:24:46:26; S12. CeO2-LDHs was added to tetrahydrofuran, and stirred to mix uniformly to prepare CeO2-LDHs suspensions of different concentrations, wherein the concentration of the high-concentration CeO2-LDHs suspension was 5wt%, and the concentration of the low-concentration CeO2-LDHs suspension was 2.5wt%; S13. The polyvinyl chloride and the photosensitizer are dissolved in tetrahydrofuran to obtain a PVC solution, wherein the concentration of the polyvinyl chloride in tetrahydrofuran is 8 wt %, and CeO2-LDHs suspensions of different concentrations are added, wherein the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1, and after being stirred and dispersed uniformly, PVC-LDHs dispersions of different concentrations are obtained; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Example 4 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. The Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1.8:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film containing a low amount of CeO2-LDHs is compounded with the ABS sheet. The hot pressing temperature is 190°C on the PVC film side and 205°C on the ABS sheet side. The hot pressing time is 2 minutes and the pressure is 1.5 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain the ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After adding CeO2 to deionized water and dispersing it uniformly by ultrasonic, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added, and the mixture was heated to 95°C and stirred for 1 hour by ultrasonic, and then subjected to hydrothermal reaction at a temperature of 120°C for 2 hours to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 10:20:42:24; S12. CeO2-LDHs was added to tetrahydrofuran, and stirred to mix uniformly to prepare CeO2-LDHs suspensions of different concentrations, wherein the concentration of the high-concentration CeO2-LDHs suspension was 4wt%, and the concentration of the low-concentration CeO2-LDHs suspension was 1.8wt%; S13. The polyvinyl chloride and the photosensitizer are dissolved in tetrahydrofuran to obtain a PVC solution, wherein the concentration of the polyvinyl chloride in tetrahydrofuran is 6 wt %, and CeO2-LDHs suspensions of different concentrations are added, wherein the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1, and after being stirred and dispersed uniformly, PVC-LDHs dispersions of different concentrations are obtained; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Example 5 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. The Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1.5:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film containing a low amount of CeO2-LDHs is compounded with the ABS sheet. The hot pressing temperature is 190°C on the PVC film side and 200°C on the ABS sheet side. The hot pressing time is 2 minutes and the pressure is 2 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain an ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After adding CeO2 to deionized water and dispersing it uniformly by ultrasonic, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added, and the mixture was heated to 90°C and stirred for 1.5h by ultrasonic, and then subjected to hydrothermal reaction at a temperature of 115°C for 2.5h to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 11:22:44:25; S12. CeO2-LDHs was added to tetrahydrofuran, and stirred to mix uniformly to prepare CeO2-LDHs suspensions of different concentrations, wherein the concentration of the high-concentration CeO2-LDHs suspension was 4.5wt%, and the concentration of the low-concentration CeO2-LDHs suspension was 2wt%; S13. The polyvinyl chloride and the photosensitizer are dissolved in tetrahydrofuran to obtain a PVC solution, wherein the concentration of the polyvinyl chloride in tetrahydrofuran is 7 wt %, and CeO2-LDHs suspensions of different concentrations are added, wherein the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1, and after being stirred and dispersed uniformly, PVC-LDHs dispersions of different concentrations are obtained; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Comparative Example 1 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. The Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1.5:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film with a high CeO2-LDHs content is compounded with the ABS sheet. The hot pressing temperature is 190°C on the PVC film side and 200°C on the ABS sheet side. The hot pressing time is 2 minutes and the pressure is 2 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain an ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After adding CeO2 to deionized water and dispersing it uniformly by ultrasonic, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added, and the mixture was heated to 90°C and stirred for 1.5h by ultrasonic, and then subjected to hydrothermal reaction at a temperature of 115°C for 2.5h to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 11:22:44:25; S12. CeO2-LDHs was added to tetrahydrofuran, and stirred to mix uniformly to prepare CeO2-LDHs suspensions of different concentrations, wherein the concentration of the high-concentration CeO2-LDHs suspension was 4.5wt%, and the concentration of the low-concentration CeO2-LDHs suspension was 2wt%; S13. The polyvinyl chloride and the photosensitizer are dissolved in tetrahydrofuran to obtain a PVC solution, wherein the concentration of the polyvinyl chloride in tetrahydrofuran is 7 wt %, and CeO2-LDHs suspensions of different concentrations are added, wherein the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:1, and after being stirred and dispersed uniformly, PVC-LDHs dispersions of different concentrations are obtained; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high concentration of PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low concentration of PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Comparative Example 2 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. The Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1.5:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film containing CeO2-LDHs is compounded with the ABS sheet. The hot pressing temperature is 190°C on the PVC film side and 200°C on the ABS sheet side. The hot pressing time is 2 min and the pressure is 2 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain the ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. After CeO2 is added to deionized water and dispersed uniformly by ultrasonication, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea are added and stirred at 90°C for 1.5h by ultrasonication, and then hydrothermally reacted at a temperature of 115°C for 2.5h to obtain CeO2-LDHs, wherein the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea is 11:22:44:25; S12. CeO2-LDHs is added to tetrahydrofuran, stirred and mixed uniformly, and a CeO2-LDHs suspension with a concentration of 4.5wt% is prepared; S13. The polyvinyl chloride and the photosensitizer were dissolved in tetrahydrofuran to obtain a PVC solution, the concentration of polyvinyl chloride in tetrahydrofuran was 7wt%, and the CeO2-LDHs suspension was added, the volume ratio of the PVC solution to the CeO2-LDHs suspension was 1:1, and the mixture was stirred and dispersed uniformly to obtain a PVC-LDHs dispersion; S14. The sodium alginate solution is first sprayed on a glass sheet, and then the PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, it is dried. The PVC-LDHs material is immersed in water to remove the sodium alginate. Finally, it is UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure. Comparative Example 3 The preparation method of the aging-resistant high-strength ABS composite material comprises the following steps: S1. The Mg-Al-LDHs and ABS rubber powder were mixed, the mass ratio of Mg-Al-LDHs and ABS rubber powder was 1.5:100, the blend was mixed by a three-screw extruder, and then granulated by shearing granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. The ABS sheet and the gradient structure layered metal oxide PVC film are hot-pressed by a hot press, and one side of the PVC film with low LDHs content is compounded with the ABS sheet. The hot pressing temperature is 190°C on the PVC film side and 200°C on the ABS sheet side. The hot pressing time is 2 minutes and the pressure is 2 MPa. After hot pressing, the ABS composite material is water-cooled, molded, trimmed, and finally dried in an oven to obtain the ABS composite material. The preparation method of the anti-ultraviolet layer comprises the following steps: S11. Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were ultrasonically heated and stirred at 90°C for 1.5 h, and then hydrothermally reacted at a temperature of 115°C for 2.5 h to obtain LDHs, wherein the molar ratio of Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea was 22:44:25; S12. Add LDHs to tetrahydrofuran, stir and mix evenly, and prepare LDHs suspensions of different concentrations, wherein the concentration of the high-concentration LDHs suspension is 4.5wt%, and the concentration of the low-concentration LDHs suspension is 2wt%; S13. The polyvinyl chloride and the photosensitizer were dissolved in tetrahydrofuran to obtain a PVC solution, wherein the concentration of the polyvinyl chloride in tetrahydrofuran was 7 wt %, and LDHs suspensions of different concentrations were added, the volume ratio of the PVC solution to the LDHs suspensions of different concentrations was 1:1, and after stirring and dispersing uniformly, PVC-LDHs dispersions of different concentrations were obtained; S14. First, spray the sodium alginate solution on the glass sheet, then apply the high-concentration PVC-LDHs dispersion on the sodium alginate, and after the solvent evaporates, continue to apply a layer of low-concentration PVC-LDHs dispersion. After drying, soak the composite PVC-LDHs material in water to remove the sodium alginate, and finally cross-link by ultraviolet to obtain a layered metal oxide PVC film with a gradient structure. Tensile test: Tested on a universal testing machine according to GB / T 1040-2006, the tensile rate is 50mm / min; Bending test: Tested on a universal testing machine in accordance with GB / T 9341-2008 standard, with a bending strength test rate of 10 mm / min; Izod beam notch impact test: The test is carried out on a pendulum impact tester in accordance with GB / T 1843-2008 standard, where the notch type is V-type and the retained width of the notch is 8mm. Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Example 1 72.6 79.2 2.6 Example 2 69.8 78.6 2.5 Example 3 73.1 77.1 2.5 Example 4 71.4 76.5 2.6 Example 5 72.3 78.4 2.6 Comparative Example 1 71.9 77.6 2.1 Comparative Example 2 73.0 72.1 1.9 Comparative Example 3 72.5 76.9 2.5 The samples of Examples 1-5 and Comparative Examples 1-3 were subjected to UV aging treatment using a UV aging box, and the test standard was based on GB / T16422.3-2014. The prepared specimens were placed in the UV aging box, and the temperature in the box was set to 50°C, the wavelength of UV light was 340nm, the irradiation intensity was 0.83, and the UV aging time was 10 days. The following table shows the mechanical properties after aging. Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Example 1 72.2 78.5 2.4 Example 2 69.2 78.0 2.2 Example 3 72.6 76.2 2.3 Example 4 70.5 75.4 2.3 Example 5 71.2 77.4 2.3 Comparative Example 1 68.0 70.2 1.6 Comparative Example 2 67.5 65.3 1.2 Comparative Example 3 65.5 66.6 1.8 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An aging-resistant high-strength ABS composite material, characterized by: The ABS composite material comprises an anti-ultraviolet layer and an ABS layer, wherein the anti-ultraviolet layer is composed of a layered metal oxide PVC film with a gradient structure.

2. The aging-resistant high-strength ABS composite material according to claim 1, characterized in that: The preparation method of the anti-ultraviolet layer comprises the following steps: S11. CeO2 was added to deionized water and ultrasonically dispersed uniformly, and then Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea were added and stirred with ultrasonic heating, and then hydrothermally reacted to obtain CeO2-LDHs; S12. CeO2-LDHs was added to tetrahydrofuran, stirred and mixed evenly, and CeO2-LDHs suspensions with different concentrations were prepared; S13. The polyvinyl chloride and the photosensitizer were dissolved in tetrahydrofuran to obtain a PVC solution, and CeO2-LDHs suspensions of different concentrations were added, and the suspensions were stirred and dispersed uniformly to obtain PVC-LDHs dispersions of different concentrations; S14. The sodium alginate solution is first sprayed on a glass sheet, and then a high-concentration PVC-LDHs dispersion is coated on the sodium alginate. After the solvent evaporates, a layer of low-concentration PVC-LDHs dispersion is continuously coated. After drying, the composite PVC-LDHs material is immersed in water to remove the sodium alginate, and finally UV cross-linked to obtain a layered metal oxide PVC film with a gradient structure.

3. The method for preparing the aging-resistant high-strength ABS composite material according to claim 2, characterized in that: The following steps are involved: S1. Mixing Mg-Al-LDHs and ABS rubber powder, mixing the blend using a three-screw extruder, and then shearing and granulating the mixture using a granulator; S2. The blend is cast using a casting machine to obtain an ABS sheet; S3. Use a hot press to hot-press the ABS sheet and the gradient structure layered metal oxide PVC film, and compound one side of the PVC film with low CeO2-LDHs content with the ABS sheet. After hot pressing, water-cool, mold opening, trimming, and finally drying in an oven to obtain an ABS composite material.

4. The aging-resistant high-strength ABS composite material according to claim 2, characterized in that: In the step S11, the molar ratio of CeO2, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and urea is 9-13:18-25:40-50:22-28, the temperature of heating and stirring is 85-95°C, the time is 1-2h, and the temperature of hydrothermal reaction is 110-120°C, and the time is 2-3h.

5. The aging-resistant high-strength ABS composite material according to claim 2, characterized in that: In the step S12, the concentration of the high-concentration CeO2-LDHs suspension is 3.5-5.5wt%, and the concentration of the low-concentration CeO2-LDHs suspension is 1.5-3wt%.

6. The aging-resistant high-strength ABS composite material according to claim 2, characterized in that: In the step S13, the concentration of polyvinyl chloride in tetrahydrofuran is 5-8wt%, and the volume ratio of the PVC solution to the CeO2-LDHs suspensions of different concentrations is 1:

1.

7. The method for preparing the aging-resistant high-strength ABS composite material according to claim 3, characterized in that: In the step S1, the mass ratio of Mg-Al-LDHs to ABS rubber powder is 1-2:

100.

8. The method for preparing the aging-resistant high-strength ABS composite material according to claim 3, characterized in that: In step S3, the hot pressing adopts different upper and lower hot pressing temperatures. The hot pressing temperature on the PVC film side is 180-190°C, and the hot pressing temperature on the ABS sheet side is 190-210°C. The hot pressing time is 1.5-3 minutes and the pressure is 1-3Mpa.

Citation Information

Patent Citations

  • Surface-protective film

    JP1996012953A

  • Door sheet manufacturing device

    KR102315770B1